KESHYA DRAVYAS FROM MADANAPALA NIGHANTU-A REVIEW - Raghuveer; Swathi P Diwakaran; Nagesh Kumar S; Akshata T S (International Journal of Applied Ayurved Research, 2018)
Hair plays an important role in maintaining beauty. Keshya-the drugs which are beneficial for hair, make the hair healthy and maintain normal colour of hair. Another meaning of keshya is the one which is ‘suitable to hair’. Khalitya (complete hair loss), palitya (graying of hair) are the burning issues affects the beauty of a person. Keshya drugs are beneficial for maintenance of healthy hair as well as normal colour. Single drug therapy (Ekamoolika prayoga) has been found in Ayurveda literature, more elaborately explained in Nighantus of Ayurveda. Madanapala Nighantu is one among them. Here the herbs possess the keshya propery are compiled from the text Madanapala Nighantu and discussed.